Special Issue "GPCRs: Ligands and beyond 2022" - Erika Cione; Maria Cristina Caroleo (MDPI AG, 2022)
The human genome encodes more than 800 different G protein-coupled receptors (GPCRs), uncovering their importance in human physiology [...]